An investigation of the bluish material on Ceres. Issue 4 (18th February 2017) - Stephan, K.; Jaumann, R.; Krohn, K.; Schmedemann, N.; Zambon, F.; Tosi, F.; Carrozzo, F. G.; McFadden, L. A.; Otto, K.; De Sanctis, M. C.; Ammannito, E.; Matz, K.‐D.; et al.
Abstract: The dwarf planet Ceres shows spatially well‐defined regions, which exhibit a negative (blue) spectral slope between 0.5 and 2.5 µm. Comparisons with planetary bodies known to exhibit a blue slope and spectral properties of materials identified on Ceres's surface based on infrared wavelength signatures indicate that the spectral changes could be related to physical properties of the surface material rather than variations in its composition. The close association of bluish surface regions to fresh impact craters implies a possible relationship to an impact‐triggered alteration and/or space weathering processes. The bluish regions could be linked with blankets of ultrafine grains and partly amorphous phyllosilicates, which form larger agglomerates due to the sticky behavior of impact‐induced phyllosilicate dust and/or the amorphization of the ejecta material during the impact process. Space weathering processes (micrometeoritic impacts, temperature changes) cause a reversal of the agglutination process and a recrystallization of the surface material with time resulting in a reddening of the spectral slope. Key Points: Ceres shows extended spectrally blue‐sloped regions similar to B‐type asteroids Ceres's blue‐sloped material is closely related to morphologically fresh impact craters Blue slope may be caused by changing physical properties (grain size/crystallinity) due to brecciation, grinding, and amorphization/melting